In network processing for tectonic monitoring - Tran, Hoang Ha (2014)
The wireless mesh network connection between GPS stations empowers them with the ability to share information and adjustments with each other in real-time. The main fo-cus of this research is to utilize wireless mesh network with three main directions 1) com-munication bandwidth reduction, 2) real-time event detection and 3) in-network GPS data processing.